THE DYNAMICS OF THE LIABILITY OF FOREIGNNESS: A GLOBAL STUDY OF SURVIVAL IN FINANCIAL SERVICES - Zaheer, Srilata; Mosakowski, Elaine (Strategic Management Journal, 1997)
We study the impact of ‘foreignness’ on survival in interbank currency trading worldwide over the period 1974–93. In particular, we develop hypotheses on the behavior of the liability of foreignness over time, and on the consequences of evolving sources of firm-level competitive advantage on this liability. We test these hypotheses on the population of 2667 market-making trading rooms located in 47 countries worldwide that either existed in 1974 or entered the industry between 1974 and 1993. The results show that there is a liability of foreignness, and that it changes over time. Further, strategic and organizational factors such as the adoption of technology by these firms and their mode of internal control significantly influenced survival, as did location-related factors such as the intensity of local and foreign competition. © 1997 by John Wiley & Sons, Ltd.